Analisis Perbandingan Penelitian Internasional-Nasional Tentang Pendidikan Multikultural Berbasis Budaya Lokal: Tantangan, Pendekatan, dan Implikasinya - Hadirman, Hadirman (Lembaga Yasin AlSys, 2025)
Although multicultural education based on local culture is an important issue at the national and international levels, there are still gaps in its implementation. The purpose of this study is to examine the differences in approaches to multicultural education at the national and global levels and to emphasize the difficulties and opportunities associated with implementing this approach. Relevant national and international journals were analyzed to conduct a literature study. Data were analyzed qualitatively using a comparative method after being collected from various scientific articles. The results of the study indicate that the global approach emphasizes more on experience-based education and interculturalism, while the national approach tends to incorporate local cultural values ​​into the school curriculum. This tendency is a form of adaptation and contextualization of multicultural education rooted in the socio-cultural context. On the other hand, policies, synergies, assumptions, cultural dominance, and antipathy towards curriculum adaptation/adjustment are problems in optimizing multicultural education. Although there are still problems in its implementation, in several studies multiculturalism has been shown to increase understanding of cultural differences, strengthen inclusivity, and create social harmony if supported by strong policies and effective learning approaches. To address the dynamics of diversity in the era of globalization, this study offers insights to educators, policymakers, and academics to build a more inclusive and locally-based education system.